Aussichten für die Kabeljausaison 1977/78 in der Deutschen Bucht nicht ungünstig - Lamp, F. (1977)
Johann Heinrich von Thunen-Institute, Federal Research Institute for Rural Areas, Forestry and Fisheries began publishing the Informationen aus der Fischereiforschung – Information on Fishery research in 2010